A cluster randomized controlled trial to reduce office workers’ sitting time: effect on productivity outcomes - Peterman, James E; Healy, Genevieve N; Winkler, Elisabeth AH; Moodie, Marj; Eakin, Elizabeth G; Lawler, Sheleigh P; Owen, Neville; Dunstan, David W; LaMontagne, Anthony D (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVE ': 'This study aimed to evaluate the impact of the Stand Up Victoria intervention – a multicomponent workplace intervention that successfully reduced workplace sitting – on productivity in the short- and longer-term. ' ' METHODS ': 'Desk-based workers [5–39 per worksite; 68% women; mean age 45.6 (standard deviation 9.4) years] were cluster randomized by office worksite to receive intervention (7 worksites, 136 workers) or control (7 worksites, 95 workers). The intervention used organizational-, environmental-, and individual-level approaches to address workplace sitting. Productivity outcomes were measured via the Health and Work Questionnaire (HWQ; 10 outcomes) and Work Limitations Questionnaire (WLQ; 5 outcomes), administered at 0 (baseline), 3 (initial), and 12 (long-term) months. Intervention effects were assessed by linear mixed models, accounting for repeated measures and clustering, baseline values, and potential confounders. Evaluable case and multiple imputation analyses were used. ' ' RESULTS ': 'At 12 months, trends for improvement were observed in the HWQ non-work satisfaction subscale (P=0.053) and stress item (P=0.086). Intervention effects on remaining outcomes for the HWQ were small and non-significant at both timepoints. At 3 months, intervention effects showed significant improvements in the WLQ mental demands subscale (P=0.043). At 12 months, intervention effects showed significant (P<0.05) small-to-moderate improvements in four WLQ outcomes (weighted total score, time-, mental-, and output demands), with physical demands showing a small significant worsening. Conclusions were robust to missing data assumptions. ' ' CONCLUSIONS ': 'The intervention improved some measures of productivity at 12 months, providing important evidence to the business case supporting workplace sitting-reduction interventions.
Keywords: cluster randomized controlled trial; intervention; occupation; office worker; physical activity; productivity; randomized controlled trial; RCT; sedentary; sitting; sitting time; Stand Up Victoria; workplace